An assessment of female executives’ influence on bank performance in Indonesia based on critical mass theory - Buchdadi, Agung Dharmawan; Suherman, Suherman; Mahfirah, Titis Fatarina; Usman, Berto; Kurniawati, Herni (International Journal of Management and Sustainability, 2023)
This study examines how female executives affect bank performance in Indonesia’s emerging market. It also investigates whether a critical mass of females on the board of management impacts bank performance. The sample was obtained from 29 banks, which covers 64.5% of publicly listed banks in Indonesia, for the observation period of 2010–2019. This study employs balanced panel data regression analysis, including the year fixed effect. Five surrogate indicators were used for female executives: female Chief Executive Officer (CEO), female Chief Financial Officer (CFO), the presence of females on the board of management, the proportion of female members on the board of management, and the number of female members on the board of management. Critical mass is reached if there are three or more female members on the board of management. The findings suggest that female executives do not significantly impact bank performance. The critical mass suggests a similar result. The findings are consistent and robust for the additional analysis using a lagged independent variable. Nevertheless, the results show that female CEOs positively impact return on assets (ROA) and return on equity (ROE). Empirical findings in Indonesia suggest that female executives do not affect bank performance. The absence of this effect is likely due to unique aspects of Indonesian culture and the structural ownership of firms. However, female CEOs were shown to improve ROE. The findings imply that females are more risk-averse decision makers than males and tend to choose lower-risk investments, which can improve ROA and ROE.